Bioactive Flavonol C-Glycoside from Sida cordifolia L. and its Molecular Docking Study - Islam, Md. Din; Mitra, Shyama Prasad; Rabi, Saswata; Hossain, Emdad; Sutradhar, Ranajit Kumar (Asian Journal of Chemistry, 2023)
Phytochemical studies of the aerial parts of Sida cordifolia L. has led to the isolation of a new flavonol C-glycoside, 3′-(3′′,7′′-dimethyl-2′′,6′′-octadiene)-8-C-β-D-glucosyl-kaempferol-3-O-β-D-galactoside (1) together with two known flavonoids, luteolin and quercetin. The structures of all the compounds were established on the basis of chemical and spectroscopic studies. Compound 1 was assessed to check the analgesic and anti-inflammatory activities and showed significant activities. Molecular docking study was conducted for compound 1 against 4O1Z protein receptor, which strongly support the in vitro biological findings.